The Cartography of Childhood. A Parcours of Philosophy for Children / Community and Cartography - Bevilacqua, Silvia (ETHICS IN PROGRESS, 2019)
The following reflections are born from some practical and theoretical trajectories undertook by the writer – already since a few years in my research scope – around philosophy for children/community and philosophical practices. The experience of some activities proposed at the Liceo Vasco/Beccaria/Govone in Mondovì during the Cespec Summer School 2017 around the issue of Humanitas in the contemporary society was recently added to these reflections. It is a theme that engaged us in several experiences of Philosophy for Community. Throughout these gatherings, we proposed a cartographic writing and philosophical approach. In particular, this contribution will explore the concept of children cartography (cartografia d’infanzia), as an occasion of translating the philosophical discourse into a map of a philosophical debate, also mutuating the concept of philosophical confluence considered by Pierpaolo Casarin. The adopted perspective is the transdisciplinary border where human geography, philosophy, and writing, as disciplinary subjects, can confound their identities and boundaries in a space of immanence in the making. Summarizing, we intend to highlight the themes, concepts, and practical propositions around some practical and theoretical research trajectories, current and future, which hold implications for all of us (and for humanity). Such practices allow again – and still – the possibility of orienting and losing oneself thanks to the Humanitas.